(untitled) (Research, Society and Development, 2022)
Infantile hemangioma (HI) is a benign vascular tumor formed during the embryonic phase. It is an active lesion in the first months of development, after which it tends to stagnate, regress, or even disappear. However, it can result in local tissue damage when there is ulceration or bleeding. The objective of this work was to study, through a retrospective study, the prevalence of HI in early childhood. A total of 93,950 reports of anatomopathological diagnoses issued by the Laboratory of Surgical Pathology at FOUSP between the years 2000 and 2021 were analyzed. For this age group, 250 files were found (250/93950; 0.26%), of which 120 were female children (120/250, 48%) and 130 male children (120/250, 52%). Infantile hemangioma was found in 3 patients (3/250, 1.2%), with 2 cases occurring in boys and 1 in a girl. Regarding location, two cases were on the tongue, and one patient was on the upper lip. Clinical knowledge of the differential diagnosis of HI is essential to establish the best approach in each case. These lesions are rarely submitted to biopsy, so the frequency can be considered low in this study.